A Novel Approach to Treat Traumatized Alveolar Ridges: Two Case Reports - Mahesh Verma; Sneha Menghani; Jyoti Devi; Rekha Gupta; Shubhra Gill (Hindawi Limited, 2016)
Functional forces are transmitted to the basal seat mucosa through a hard denture base during mastication. Such hard base dentures are not comfortably tolerated in patients with fragile oral mucosa and will cause sore spots, masticatory pain, and further resorption of alveolar bone. Soft liners materials can be advocated successfully to manage such clinical situations. The soft liner material absorbs masticatory forces by means of the cushioning effect and distributes occlusal forces uniformly to prevent trauma to compromised residual ridges.